The effect of carbonyl cyanide m-chlorophenyl-hydrazine on antibiotic susceptibility in MDR Enterobacteriaceae isolates in Babylon, Iraq - Hadeel Qasim Jebur; Alaa H. Al-Charrakh (Medical Journal of Babylon)
Abstract Background: One of the efflux pump inhibitors is carbonyl cyanide 3-chlorophenylhydrazone (CCCP) that has often been found to increase the susceptibility of a number of multi-drug resistant (MDR) MDR bacteria, isolated from human clinical specimens. Objectives: To investigate the role of active efflux system to aminoglycoside and quinolones resistance in clinical isolates of Enterobacteriaceae using the efflux pump inhibitor CCCP. Materials and Methods: Enterobacteriaceae isolates were recovered from different clinical samples from hospitalized patients. The minimum inhibitory concentrations (MICs) of antibiotics (levofloxacin, ciprofloxacin, and gentamycin) were compared with and without the efflux pump inhibitor (CCCP) in order to confirm the effective role of the efflux pump in our isolates. Results: The results found that out of 280 clinical samples, only 134 (47.1%) isolates belonged to Enterobacteriaceae. Polymerase chain reaction (PCR) results showed that six (42.8%) out of 14 selected MDR isolates were positive for efflux pump gene oqxA. However, no isolates showed positive results for the efflux pump oqxB. The results of MIC for 14 Enterobacteriaceae isolates against these three antibiotics showed that all isolates had MIC ≥128 μg/mL in the absence of CCCP for levofloxacin, ciprofloxacin, and gentamycin. The results showed the MIC of levofloxacin and ciprofloxacin were reduced for isolates, and the growth of bacteria was inhibited in presence of the CCCP. However, all Enterobacteriaceae isolates showed high MIC values (≥128) even in the presence of the CCCP which indicates no effect the inhibitor in reducing the MIC of the isolates for Gentamycin. Conclusion: From this study, we can conclude that high prevalence of efflux pumps gene (oxqA) was detected among MDR and XDR Enterobacteriaceae isolates and the efflux pump inhibitor (CCCP) has a positive effect and improves the sensitivity of MDR isolates to ciprofloxacin, levofloxacin but not gentamicin.